The use of Social Media to enhance Self-directed Learning (SDL) in English - Nurianti Sitorus (Proceeding International Conference on Religion, Science and Education, 2023)
Social media is not only used as a medium to socialize but it also has been utilized in educational areas to transfer the knowledge which is commonly done in a class. English as one of the subject studied in polytechnic is potentially taught by using social media such as Instagram. One of the advantages of using Instagram is that the learners can study independently from posts, stories, reels or any menus on it. Moreover, some accounts are verified which means that they use proper English with correct grammar and high vocabularies which enrich students knowledge when learning. As one of skills in 21st , students should obtain the self-directed learning (SDL) which instagram can facilitate to enrich their English. In this present study forty students from Politeknik Teknik Negeri Media Kreatif are taken as respondents to answer some questions regarding the use of instagram in self-directed learning. Besides that, formerly, the participants have been taught by using Instagram posts from verified accounts such as VOA, BBC and The Heralds. Qualitative Method is applied to gain the data from the participants. It is found that there is a significant improvement in their academic score and the students are better in self-directed learning. In the making of self-directed learning to create independent learners, the use of social media is suggested especially with the occurrence of lots of trustable accounts and applications. By doing so, studying English would not just done when the instructors or teachers are in, but anywhere and anytime. Furthermore, the learners can also arrange, proceed and measure their own study process. Therefore, social media is prospective in directing students to study English and be an independent learner.